PARTICIPATORY MONITORING OF WATER QUALITY IN A COASTAL LAGOON: INTEGRATING CITIZEN SCIENCE AND ENVIRONMENTAL EDUCATION THROUGH DIGITAL MEDIA - Lopes, Michelle das Neves; Marques, Bruno Rafael; Petrucio, Mauricio Melo; Leite, Nei Kavaguichi (Geosaberes; Vol 16 (2025), 2025)
The participatory monitoring of water quality in a coastal lagoon, conducted by public school students and made accessible to the community through a digital application with a QR code, represents an innovative strategy that integrates citizen science and educommunication. Over four months, students actively engaged in the collection and analysis of limnological parameters, linking school curriculum with scientific practice and enhancing the understanding of local ecology. The results demonstrate that this approach strengthens community engagement and environmental awareness, fostering behavioral changes aimed at the sustainable management of water resources. Disseminating the findings through digital media expanded the reach of environmental information and encouraged social participation in territorial governance, particularly within protected areas. This initiative contributes to the development of environmentally conscious citizens, promotes participatory management of conservation units, and reinforces urban planning and climate resilience.